Sustainable Development of Mountain Tourism in Georgia - Maka Piranashvili; Shorena Metreveli; Lizi Dzimistarishvili (European Scientific Journal, ESJ, 2026)
Mountain tourism is a rapidly growing sector in Georgia, and the role of mountain and ski resorts in the development of the country’s tourism. Sustainable development of mountain tourism is one of the resources for economic growth in Georgia; furthermore, it is an important prerequisite for regional development, strengthening social capital and protecting natural heritage. The paper discusses the economic benefits derived from the visits of international travelers and the necessary conditions for sustainable development, and evaluates the influence of the number of visitors to Georgia and the income derived from international tourism based on statistical analysis. For this purpose, correlation-regression and dynamic analysis methods were used. Through secondary quantitative and qualitative research, we discussed important aspects necessary for the creation of sustainable mountain tourism in the country, for which an in-depth study was conducted. Consequently, several key problems were identified: insufficient infrastructure development, environmental threats, uneven distribution of tourism revenues, and limited involvement of the local population. The goal of the article is to analyze the development of sustainable mountain tourism, where one of the priority areas is the transformation of seasonal resorts into four-season resorts. All the above should be realized in accordance with the goals and recommendations of sustainable development.